The Role of Historical Christian Missions in the Location of World Bank Aid in Africa - Alpino, Matteo (World Bank, Washington, DC, 2020)
This article documents a positive and sizable correlation between the location of historical Christian missions and the allocation of present-day World Bank aid at the grid-cell level in Africa. The correlation is robust to an extensive set of geographical and historical control variables that predict settlement of missions. The study finds no correlation with aid effectiveness, as measured by project ratings and survey-based development indicators. Mission areas display a different political aid cycle than other areas, whereby new projects are less likely to arrive in years with new presidents. Hence, political connections between mission areas and central governments could be one likely explanation for the correlation between missions and aid.